Prediksi Harga Saham dengan Menggunakan Algoritma Regresi Linear - Khasanah, Uswatun (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Stock investment is the most popular form of investment. Investors need to observe changes stock prices in the time series to find out stocks movement. Therefore, one way to find out stock price estimates can be done by predicting using methods, models that must be tested for accuracy. The aim is to predicting stock prices and transmit the prediction results obtained. The method used in this research is the Linear Regression Algorithm. This algorithm was chosen because it’s able estimates using historical data and can produce a pattern that is interconnected with each variable used. The data used in this research is 1,717 share price data PT Bank Mandiri Tbk. (BMRI.JK). Data obtained from 01 January 2018 to 10 December 2024. There are 5 variables, including 4 independent variables namely Date, Open, High, Low, and the dependent variable is Close. The results obtained MAPE 0.54%, RMSE 38.39, and MSE 1473.84